Histological verification of the prehypogastric and ovarian ganglia confirms a bilaterally symmetrical organization of the ganglia comprising the aortic plexus in female human cadavers. Issue 5 (11th January 2016) - Beveridge, Tyler S.; Johnson, Marjorie; Power, Nicholas E.; Allman, Brian L.
Abstract: The aortic plexus is a network of sympathetic nerves positioned along the infrarenal abdominal aorta. Recently, we characterized the aortic plexus and its ganglia (inferior mesenteric, left/right spermatic, and prehypogastric ganglion) in males; however, the literature minimally describes its anatomy in females. In the present study, we conducted the first histological examination of the left and right ovarian ganglia, while also investigating whether females, like males, exhibit a prehypogastric ganglion. The ganglia were dissected from embalmed ( n = 32) and fresh ( n = 1) human cadavers, and H&E staining was used to confirm the presence of a left ovarian ganglion in 31/31 specimens, a right ovarian ganglion in 29/29 specimens and a prehypogastric ganglion in 25/28 specimens. Comparable to the topographic arrangement in males, there is a bilateral organization of the ganglia comprising the aortic plexus in females. More specifically, the left and right ovarian ganglia were positioned in close relation to their respective ovarian artery, whereas the prehypogastric ganglion was positioned within the right cord of the aortic plexus, contralateral to the inferior mesenteric ganglion. Using immunohistochemistry, it was shown that all ganglia from the fresh cadaver stained positive for tyrosine hydroxylase, thereby confirming their sympathetic nature. Having provided the first topographical and histological characterization of the ovarian and prehypogastric ganglia in females, future studies should seek to determine their specific function.